Werbalne sposoby komunikowania „dociekliwości” przez felietonistów (Piotra Zarembę, Magdalenę Środę i Szymona Hołownię). Wyniki badań empirycznych - Barańska-Szmitko, Anna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The main research problem presented in this paper is the communication of one of many features of personal image – the trait ‘inquisitive’. The paper presents the results of the research which used quantitative methods and discourse analysis in order to examine what image can be created when somebody is talking/writing about various subjects but not about him/herself. The results of the research shows that it is possible to indicate six ways of communicating“inquisitiveness”: questions, declaration of interest, declaration of information searching, insight/conclusion, multifaceted issue, details.